Men and Boys: Sharing the Skills Across Generations. Issue 1 (2nd January 2017) - Golding, Barry; Foley, Annette
ABSTRACT: Our paper focuses on intergenerational learning in informal community settings between older men and boys. It examines and challenges narrow definitions of the notion of what is meant by "older" and "intergenerational" learning. It stresses the importance of older men's capacity to be contemporary in their worldview, while drawing from a deep knowledge and wisdom developed from their life experiences and also from their formative cultural, national, and Indigenous learning traditions. Our paper provides an account of intergenerational stories wherein men informally mentor, share skills, and develop meaningful relationships with disengaged and disconnected young people in the community Men's Sheds.